2003
DOI: 10.1007/s00276-003-0101-6
|View full text |Cite
|
Sign up to set email alerts
|

A study of reproducibility of an original method of CT measurement of the lateralization of the intertubercular groove and humeral retroversion

Abstract: An original method of CT measurement of the lateralization of the humeral intertubercular groove is described based on geometric construction following Thales theorem. A study of intra- and interobserver reproducibility was done of this measurement and humeral retroversion on 32 healthy volunteers. The results show good reproducibility of these measurements. The average value of humeral retroversion was lower than the average values found in the literature: 11.71 degrees on average on the dominant side and 7.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
23
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 23 publications
4
23
1
Order By: Relevance
“…In our study, the mean humeral retroversion angle of 12.31°confirms other anatomical studies, which found mean normal values that were quite variable, from 9°to 40° [3,6]. This variation is due to several factors, including the definition of humeral head retroversion, different methods of measurement, ranges of normal values, and accuracy of anatomic landmarks to guide determination of anatomic retroversion.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In our study, the mean humeral retroversion angle of 12.31°confirms other anatomical studies, which found mean normal values that were quite variable, from 9°to 40° [3,6]. This variation is due to several factors, including the definition of humeral head retroversion, different methods of measurement, ranges of normal values, and accuracy of anatomic landmarks to guide determination of anatomic retroversion.…”
Section: Discussionsupporting
confidence: 88%
“…Humeral head retroversion is generally defined with respect to the plane of the humeral head articular surface proximally; distally, however, the reference axis has been debated, including the transepicondylar axis [3,4,8], trochlear tangent axis [7,9,14,19] and forearm axis [8,18]. Methods of measurement have included direct anatomic [13,15], radiographic [4,14], ultrasound [10], computed tomography scan [3,8], MRI [6], and computer-assisted methods [5,19,21,22]. Boileau et al [2] showed that the radiographic method overestimated the humeral head retroversion relative to the computer-assisted method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors calculated the average HTA in 32 healthy volunteers (17 females and 15 males between 22 and 44 years of age) as 11.71° on the dominant and 7.03° on the nondominant side. Consequently, they demonstrated that the CT measurement method was repeatable and that such measurements would be useful in shedding light on the pathophysiology of chronic anterior shoulder instability (16).…”
Section: Discussionmentioning
confidence: 99%